2020
DOI: 10.1101/2020.01.14.905620
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Corollary Discharge versus Efference Copy: Distinct Neural Signals in Speech Preparation Differentially Modulate Auditory Responses

Abstract: Actions influence sensory processing in a complex way to shape behavior. For example, it has been hypothesized that during actions, a copy of motor signals-termed corollary discharge or efference copy-can be transmitted to sensory regions and modulate perception. Such motor-to-sensory transformation has been evident among animal species and is extended to human speech production and control. The inhibitory function of the motor copies has been supported by the suppression of sensory responses during action exe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 77 publications
4
16
1
Order By: Relevance
“…For example, orofacial motion alters speech perception, such as the McGurk effect (McGurk and MacDonald, 1976), and shortens latency of early auditory responses (Van Wassenhove et al, 2005). Speech articulation dampens the auditory responses to speech feedback (Houde et al, 2002) and modulates the sensitivity to auditory stimuli via the motorto-sensory transformation (Tian and Poeppel, 2010, 2013, 2015Tian et al, 2016Tian et al, , 2018Ma and Tian, 2019;Li et al, 2020). The current study provides evidence supporting that the language system can penetrate and influence visual processing.…”
Section: Chunking In a Broader Cognitive Perspectivesupporting
confidence: 54%
“…For example, orofacial motion alters speech perception, such as the McGurk effect (McGurk and MacDonald, 1976), and shortens latency of early auditory responses (Van Wassenhove et al, 2005). Speech articulation dampens the auditory responses to speech feedback (Houde et al, 2002) and modulates the sensitivity to auditory stimuli via the motorto-sensory transformation (Tian and Poeppel, 2010, 2013, 2015Tian et al, 2016Tian et al, , 2018Ma and Tian, 2019;Li et al, 2020). The current study provides evidence supporting that the language system can penetrate and influence visual processing.…”
Section: Chunking In a Broader Cognitive Perspectivesupporting
confidence: 54%
“…In this study, we observed a broad sensorimotor network operating in the mu and beta rhythms during the imagined singing tasks ( Fig 3B and 3D ). These results further suggested that computations could be executed at these rhythms to internally simulate action during imagery [ 3 , 12 , 20 , 22 , 25 ]. Such motor simulations presumably generate an efference copy that is used to emulate the somatosensory consequences of actions for estimating the status of motor effectors [ 3 , 22 , 25 ].…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, our results offer insights into the functional and anatomical foundations of auditory hallucinations. We have previously hypothesized that, from a cognitive perspective, auditory hallucinations may be caused by incorrect source monitoring of internally self-induced auditory representations [ 3 , 12 ]. These results of synchronized neural activity in the frontal-parietal-temporal network suggest the possible neural pathways for the internal generation of auditory representation.…”
Section: Discussionmentioning
confidence: 99%
“…“corollary discharge” or “efferent copy” signals; (Eliades and Wang, 2013)). A recent study (Li et al, 2020) suggested a distinction between these signals: the first having an overall suppressive effect, independently of the sound being produced; the second carrying specific information about the sound generated, potentially enhancing its future processing. Thus, pre-vocal power changes in low frequencies, undistinguishable across call types, could reflect general inhibitory mechanisms in AC consistent with corollary discharges mediated by higher-order structures.…”
Section: Discussionmentioning
confidence: 99%
“…Such auditory cortical suppression is thought to be mediated by preparatory motor signals originating in the motor system (i.e. “corollary discharges” or “efference copies”; (Clayton et al, 2020; Li et al, 2020)). The attenuation of neural responses in AC during vocal production supports precise vocal control by means of feedback mechanisms (Eliades and Tsunada, 2018; Eliades and Wang, 2008), in which frontal cortical areas are also involved (Behroozmand et al, 2015; Kingyon et al, 2015; Loh et al, 2020; Toyomura et al, 2007).…”
Section: Introductionmentioning
confidence: 99%